Genomic Features and Antimicrobial Activity of Phaeobacter inhibens Strains from Marine Biofilms - Han Cui; Jie Lu; Wei Ding; Weipeng Zhang (Marine Drugs)
Members of the genus Phaeobacter are widely distributed in the marine environment and are known for their ability to produce tropodithietic acid (TDA). Studies investigating the genomic and metabolic features of Phaeobacter strains from marine biofilms are sparse. Here, we analyze the complete genomes of 18 Phaeobacter strains isolated from biofilms on subtidal stones, with the aim of determining their potential to synthesize secondary metabolites. Based on whole-genome comparison and average nucleotide identity calculation, the isolated bacteria are classified as novel strains of Phaeobacter inhibens. Further analysis reveals a total of 153 biosynthetic gene clusters, which are assigned to 32 gene cluster families with low similarity to previously published ones. Complete TDA clusters are identified in 14 of the 18 strains, while in the other 4 strains the TDA clusters are rather incomplete and scattered across different chromosome and plasmid locations. Phylogenetic analysis suggests that their presence or absence may be potentially attributed to horizontal gene transfer. High-performance liquid chromatography–mass spectrometry analysis demonstrates the production of TDA in all the examined strains. Furthermore, the Phaeobacter strains have strong antibacterial activity against the pathogenic strain Vibrio owensii ems001, which is associated with acute hepatopancreatic necrosis in South American white shrimp. Altogether, this study ameliorates our knowledge of marine biofilm-associated Phaeobacter and offers new avenues for exploiting marine antimicrobial agents.